Nanocage-incorporated engineered destabilized 3'UTR ARE of ERBB2 inhibits tumor growth and liver and lung metastasis in EGFR T790M osimertinib- and trastuzumab-resistant and ERBB2-expressing NSCLC via the reduction of ERBB2 - Awah, Chidiebere U.; Sun Mun, Joo; Paragodaarachchi, Aloka; Boylu, Baris; Nzegwu, Martin; Matsui, Hiroshi; Ogunwobi, Olorunseun (Frontiers in Oncology, 2024)
Non-small cell lung cancer (NSCLC) caused more deaths in 2017 than breast cancer, prostate, and brain cancers combined. This is primarily due to their aggressive metastatic nature, leading to more fatal rates of cancer patients. Despite this condition, there are no clinically approved drugs that can target metastasis. The NSCLC with EGFR T790Moverexpressing HER2 shows the resistance to Osimertinib and trastuzumab starting 10-18 months after the therapy, and thus prospects are grim to these patients.To target the recalcitrant ERBB2 driver oncogene, we developed two engineered destabilizing 3'UTR ERBB2 constructs that degrade the endogenous ERBB2 transcript and proteins by overwriting the encoded endogenous ERBB2 mRNA with the destabilizing message. When iron oxide nanocages (IO-nanocages) were used as vehicles to deliver them to tumors and whole tissues in mice bearing tumors, it was well tolerated and safe and caused no genome rearrangement while they were integrated into genome deserts (non-coding regions). We achieved significant reduction of the primary tumor volume with desARE3'UTRERBB2-30, achieving 50% complete tumor lysis and inhibited 60-80% of liver metastasis, hepatomegaly, and 90% of lung metastasis, respectively, through the ERBB2 downregulation. These constructs were distributed robustly into tumors, livers, lungs, kidneys, spleen and mildly in the brain and not in the heart. They caused no abnormality both in short-and long-term administrations as well as in healthy mice. In summary, we accomplished significant breakthrough for the therapeutics of intractable lung cancer patients whose cancers become resistant and metastasize.